Pragmatic functions of anglicisms in the Montenegrin language - Đurčević, Jovana; Kostić, Nataša (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper deals with the traditional distinction between necessary and unnecessary loanwords as a problematic one because it marginalises the functions of so-called unnecessary loanwords. By adopting a cognitive-linguistic approach, this paper aims to highlight the importance of both types of loanwords from a language user’s point of view. To this end, we examine anglicisms in Montenegrin on the basis of a new pragmatic model which distinguishes between catachrestic and non-catachrestic loanwords (Onysko, Winter-Froemel 2011). Our study has shown that the pragmatic distinction of anglicisms is possible in Montenegrin, thereby proving it is unacceptable to divide them into necessary and unnecessary ones. The results also show that anglicisms do not always have all the characteristics typical of their categories, which brings us back to the cognitive-linguistic approach we have taken in our study.